Treatment satisfaction, safety and effectiveness of adding methotrexate to adalimumab in patients with psoriasis responding suboptimally to adalimumab in a real‐world setting. (20th January 2022) - Papp, K.A.; Gooderham, M.J.; Albrecht, L.E.; Raymond, M.‐A.; Lynde, C.W.
Abstract :